Professional Learning Community in Malaysia - Hassan, Roslizam; Ahmad, Jamilah; Boon, Yusof (International Journal of Engineering and Technology, 2018)
The professional learning community (PLC) is a platform for teachers to share their opinions and experiences especially with respect to the quality of teaching and learningÂ processes (PdP). This partnership gives teachers more added value because they have the opportunity to improve their self-esteem and to keep in pace with the developments in the education world. This concept paper will discuss a number of issues related to PLCs such as PLC's background and development, PLC definitions, the development of PLC concept, PLC models and the issues and challenges that exist in implementing PLC. The analysis was done in the context of Malaysia and abroad. The paper is written based on extensive secondary data analysis. After examining all matters related to PLC, it can be concluded that PLC is a form of partnership that every school teacher needs to practice either in the context of education in Malaysia or anywhere in order to drive excellence in a school. With a lot of challenges nowadays regarding the implementation of PLC, this issue needs to be addressed so that the quality of teachers can be enhanced and will further influence the students' academic achievement.Â Â